2020
DOI: 10.1111/ijac.13603
|View full text |Cite
|
Sign up to set email alerts
|

Structural, morphological, and opto‐electrical properties of Y2‐xYbxO3nanoparticles synthesized using co‐precipitation method

Abstract: Ceramics are inorganic materials which are mostly crystalline oxides. The crystallinity of the ceramics differs from highly oriented crystalline to a semi-crystalline structure. Due to its varying crystallinity and electron composition in the ionic as well as covalent bonds the ceramics are able to exhibit different thermal, structural, optical, and electrical properties. Polycrystalline ceramics are used for various applications such as solid-state lasers, light-emitting diodes, infrared detectors, temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…For example, Ahlawat [37] reported the optical bandgap of sol–gel derived Y 2 O 3 nanoparticles as 5.5 eV. Further, Sushil Kumar et al [38] reported a decrease in the bandgap of Y 2– x O 3 : x Yb synthesised using the co‐precipitation method from 5.14 to 3.60 eV for a composition with x = 0.14. However, there is some exception, where the bandgap of Y 2 O 3 was found to increase after doping of Eu due to Burstein–Moss effect [39].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Ahlawat [37] reported the optical bandgap of sol–gel derived Y 2 O 3 nanoparticles as 5.5 eV. Further, Sushil Kumar et al [38] reported a decrease in the bandgap of Y 2– x O 3 : x Yb synthesised using the co‐precipitation method from 5.14 to 3.60 eV for a composition with x = 0.14. However, there is some exception, where the bandgap of Y 2 O 3 was found to increase after doping of Eu due to Burstein–Moss effect [39].…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that the peaks located at 37.28, 43.30, 62.92, 75.44, and 79.39° correspond to the (111), (200), (220), (311), and (222) planes of CeO 2 (JCPDS 65–2975). The crystallite size of CeO 2 was estimated by Scherrer's formula: DXRDbadbreak=kλβcosθ,\begin{equation}{D}_{{\rm{XRD}}} = \frac{{k\lambda }}{{\beta \cos \theta }},\end{equation}where k is a constant (.89), λ is the wavelength of X‐ray (.154056 nm for Cu‐Kα), β is the full bandwidth at half height, and θ is the diffraction peak angle 23 . The mean calculated crystallite sizes were 26.4 nm, 31.7 nm for powder synthesized with and without NH 4 NO 3, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…where k is a constant (.89), λ is the wavelength of X-ray (.154056 nm for Cu-Kα), β is the full bandwidth at half height, and θ is the diffraction peak angle. 23 The mean calculated crystallite sizes were 26.4 nm, 31.7 nm for powder synthesized with and without NH 4 NO 3, respectively. The specific surface areas and porous nature of the samples were further investigated by nitrogen adsorptiondesorption measurement.…”
Section: Characterization Of the Ceo 2 Powdersmentioning
confidence: 93%
“…From Figure 3, it is seen that the PAA-assisted particles are well spherical, while the powders without dispersant show a dumbbells-like structure, suggesting that PAA could assist to smooth the edges of the particles. The crystallite sizes of the two powders were calculated according to the Scherrer Formula, 24,25 derived from the respective measured XRD patterns. The existence of PAA does not affect the crystallite sizes of the powders but does affect the calcinated particle size slightly.…”
Section: Resultsmentioning
confidence: 99%